From Industry 4.0 to Construction 5.0: Exploring the Path towards Human–Robot Collaboration in Construction - Marinelli, Marina (Systems (Basel), 2023)
Industry 4.0 is a recent trend representing the vision for the integration of information, objects and people in cyber-physical scenarios in order to transform factories into intelligent environments. Although this transition is still ongoing, the corresponding vision of Industry 5.0 has already emerged. Industry 5.0 aims to bring the human factor back into the production system, with the collaborative work paradigm of human–robot collaboration (HRC) at its core. This paper first discusses how Industry 4.0 has conceptually evolved and is being implemented in the context of construction, through the lens of a literature review and bibliometric analysis. Additionally, it clarifies the scope of Industry 5.0 and assesses its momentum as a literature trend, drawing on bibliometric comparisons with the Industry 4.0/Construction 4.0 vision. Furthermore, it makes a realistic assessment of the potential of the Industry 5.0 paradigm to evolve into Construction 5.0. In this context, it reviews the prospects of HRC use in construction, highlights its distinct challenges and proposes new directions. This paper is, to the author’s best knowledge, the first consideration of ‘Construction 5.0’ and the first bibliometric analysis comparing data from Industry 4.0, Construction 4.0 and Industry 5.0 literature.